2019
DOI: 10.5811/westjem.2019.7.43073
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Emergency Department Recidivism in the Older Adult

Abstract: Our objective was to review risk factors predictive of older adult recidivism in the emergency department. Certain risk factors and themes commonly occurred in the literature. These recurring factors included increasing age, male gender, certain diagnoses (abdominal pain, traumatic injuries, and respiratory complaints), psychosocial factors (depression, anxiety, poor social support, and limited health literacy), and poor general health (cognitive health and physical functioning). Many of the identified risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
20
2
Order By: Relevance
“…Our findings are also contrary to the literature demonstrating that advancing age, in general, increases the odds of ED returns in older adults [1,3,24]. In a study of the general ED population within the United States, patients over 65 years of age were three times more likely to return and to be hospitalized within 72 hours of an ED visit compared with those under age 30 and twice as likely as those under age 46.…”
Section: Age As a Predictor For Pain-related Returnscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are also contrary to the literature demonstrating that advancing age, in general, increases the odds of ED returns in older adults [1,3,24]. In a study of the general ED population within the United States, patients over 65 years of age were three times more likely to return and to be hospitalized within 72 hours of an ED visit compared with those under age 30 and twice as likely as those under age 46.…”
Section: Age As a Predictor For Pain-related Returnscontrasting
confidence: 99%
“…Older adults are more likely to return to the emergency department (ED) compared with younger adults [1,2]. Numerous studies have identified risk factors for ED returns in older adults [3]. Features that may contribute to ED recidivism include poor health literacy, poor cognitive health, chronic comorbid conditions, and lack of social support [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These ED visits take longer, represent higher‐acuity illnesses, and require more intensive services, resulting in increased costs 1,3,4 . ED visits for older adults are frequently followed by adverse events such as functional and physical decline, delirium, and death, 5‐8 with risk increasing for those with advanced age, frailty, multiple chronic conditions, and other conditions prevalent among older adults (e.g., dementia) 3,7,9‐11 . Although the majority of older ED patients are discharged, they are more likely to revisit the ED than younger adults and be subsequently admitted to the hospital 3,10 .…”
Section: Introductionmentioning
confidence: 99%
“…ED visits for older adults are frequently followed by adverse events such as functional and physical decline, delirium, and death, 5‐8 with risk increasing for those with advanced age, frailty, multiple chronic conditions, and other conditions prevalent among older adults (e.g., dementia) 3,7,9‐11 . Although the majority of older ED patients are discharged, they are more likely to revisit the ED than younger adults and be subsequently admitted to the hospital 3,10 . Recent studies have shown that approximately 20% to 25% of older ED patients return within 30 days of discharge, often due to nonadherence with medications and treatment plans, not understanding discharge instructions, lack of disease knowledge, increases in symptoms, or lack of social support 6,10,12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…There are more studies that describe the hospital care of immigrants residing in Spain [36][37][38] in a more extensive way, but these do not address the healthcare needs when the boats arrive. In the same way, other studies address these same issues related to hospital care or access to specific services offered by different health systems in the context of other countries, analyzing their barriers and difficulties [39][40][41][42]. These studies emphasize that the attention needed by these populations are not limited to those presented at the time of their arrival, but, sometimes, the approach to the problems that appear later are much more complex.…”
Section: Discussionmentioning
confidence: 99%